The Use of ChatGPT in Madrasah: A Study of Arabic Teachers in Kerinci Regency and Sungai Penuh City - Eva Ardinal; Syukrawati Syukrawati; Ferki Ahmad Marlion; Sri Zulfida; Nurul Alamin (Institut Agama Islam Negeri Curup, 2026)
The use of artificial intelligence in education has grown massively, including the use of ChatGPT among teachers and students. This phenomenon presents a dilemma in educational practice, both in terms of the effectiveness of learning and the ethical implications within an academic context. This study aims to analyse the motives behind the use of ChatGPT by Arabic language teachers and its implications for the learning process. This study employs a qualitative approach with a field study design. Data were collected through interviews with Arabic language teachers and document analysis, and were subsequently analysed using data reduction, data presentation, and conclusion-drawing techniques. The research findings indicate that teachers use Arabic language learning as a supporting tool in elaborating on learning materials. Consequently, the prominent motivations for using ChatGPT tend to centre on efficiency, creativity, and collaboration. Whilst the use of ChatGPT has implications for enhancing Arabic language learning, its use also raises concerns regarding the preservation of critical thinking. This is because ChatGPT can provide data that does not align with the facts. Consequently, if teachers are not careful, they may impart false information to students. Therefore, the use of ChatGPT in the Arabic language learning process must be grounded in clear ethical principles to prevent the degradation of learning, specifically by raising teachers’ awareness to use ChatGPT more wisely. This study makes a theoretical contribution by expanding the study of the use of AI technology in Arabic language learning, particularly from the teachers’ perspective, as well as a practical contribution regarding the importance of strengthening digital literacy and the ethics of AI use in the learning process to prevent a decline in the quality of learning.